KEPUASAN KONSUMEN DITINJAU DARI HARGA, PROMOSI, DAN KUALITAS PRODUK - Adi Nugroho, Bayu Sapta; Tamrin, Moh; Christiawan, Daniel Grace (Sekolah Tinggi Ilmu Ekonomi Semarang, 2025)
This study aims to identify internal and external factors including strengths and weaknesses, as well as opportunities and threats faced by Oemah Herborist Semarang Consumers. This study also aims to determine the marketing strategy used by Oemah Herborist Semarang in facing business competition around it, as well as to understand the strategies they use to attract consumer interest. The population in this study were visitors who purchased consumer products from Semarang herbalists. The sampling technique in this study is by using census sampling, which is a sampling technique from the entire population, the sample used is 90 people. The research methods used are quantitative method methods, quantitative methods consisting of classical assumption tests, normality tests, multicollinearity tests, heteroscedasticity tests, partial significance test (t-test) and determination coefficient (R²) tests. The results of this study prove that the price variable on consumer satisfaction is obtained with a value of t = 0.854 < t table of 1.988 with a significance of 0.095 (p > 0.05). The promotion variable on consumer satisfaction was obtained with a value of t = 3,776 > t table of 1,988 with a significance of 0.000 (p < 0.05). The variable of Product Quality on Consumer satisfaction was obtained a value of t = 2,565 > t table of 1,988 with a significance of 0.012 (p < 0.05). The value of the determination coefficient (Adjusted R Square) was obtained as 0.431 which means that 43% of purchase decisions can be explained by the variables of price, promotion, and product quality, while the rest is influenced by other variables outside this research mode. Suggestion from the results obtained by the researcher that the employees of the oemah herborist beauty factory already have qualified managerial skills. However, it is good if the managerial skills are sharpened. To increase consumer satisfaction at oemah herborist beauty factory from the price perspective, the advice given to oemah herborist beauty factory is the main price given to consumers related to products, promotions and good product quality for the progress of Oemah Herborist Semarang.